Digitization, Digitalization and Digital Transformation of Procurement Processes in the Family Company Dines d. o. o. - Harambašić, Edin; Deu, Domen (Izzivi prenosa vodenja na naslednjo generacijo v družinskem podjetju, 2025)
This chapter presents a case study of digital transformation in the procurement process of the family-owned company Dines. The aim is to show how a small business in the field of air conditioning and heating systems introduces digital technologies. The research is based on a qualitative case study method and includes a semi-structured interview with the operations manager. The company implemented digital changes step by step, starting with digitized documents (invoices, work orders), and then added an ERP system and an online portal for ordering spare parts. All changes were focused on improving transparency, efficiency, and process simplicity. A key role was played by the younger generation, who brought motivation and openness to innovation. The results show that even small family businesses with limited resources can successfully introduce digital tools if they have a clear vision, internal motivation, and employee support. I conclude that gradual implementation, user focus, and inclusive communication with employees are essential for a successful digital transformation in similar business environments.